Measuring the impact of minimum wages : evidence from Latin America - Maloney, William F., 1959- 1959- (Policy research working paper, 2001)
Simple numerical measures of the minimum wage may offer deceptive indicators of its impact. Alternative measures, such as kernel density or cumulative distribution plots, are more reliable, and highlight influences higher in the wage distribution or on the informal sector. Panel employment data from Colombia, where minimum wages seem high and binding, show that the minimum wage can have important impacts on wages and unemployment across the wage distribution